The Impact of Consumer Ethnocentrism on Purchase Intentions: Local Versus Foreign Brands - Mehrukh Salman; Uswa Naeem (The Lahore Journal of Business)
This study evaluates the impact of consumer constructs, including ethnocentrism, attitudes toward brands, and celebrity endorsement, on purchase intentions for beverages in Pakistan. A quantitative survey was administered to collect the data and a path analysis conducted to test the model. Based on a sample of 150 respondents, our results indicate a positive relationship between ethnocentrism and purchase intentions with respect to local brands. Moreover, ethnocentrism, attitudes toward brands, and celebrity endorsements all have a significant impact on purchase intentions for local brands.